After innocence : visions of the Fall in modern literature - Otten, Terry; University of Pittsburgh. University Library System. Digital Research Library (Pittsburgh, Pa. : University of Pittsburgh Press, 1982)
The fear of falling, the awareness of lost innocence, lostillusions, lost hopes and intentions, of civilization indecline-these are the themes which link literature to theology,both concerned with the shape of human destiny. Otten discusses thecontinuing viability of the myth of the Fall in literature. Herelates a wide variety of romantic and modern works to fundamentalissues in modern Christianity. .
1. Introduction -- 2. A Romantic Enlightenment: Blake's Bible of Hell -- Byron's Cain -- Coleridge's "Christabel" and Shelley's The Cenci -- Conrad's "The Secret Sharer" -- 3. Childhood's End: The Turn of the Screw by Henry James -- The Lord of the Flies by William Golding -- 4. Civilization and its Discontents: Heart of Darkness by Joseph Conrad -- Demian by Hermann Hesse -- 5. The Fall and After: La Chute by Albert Camus -- After the Fall by Arthur Miller -- 6. The Fall in Fantasy: Alice in Wonderland and Through the Looking Glass by Lewis Carroll -- 2001: a Space Odyssey by Stanley Kubrick and Arthur C. Clarke -- 7. Running the Risk: Who's Afraid of Virginia Woolf? by Edward Albee -- Deliverance by James Dickey -- 8. Conclusion.
Includes bibliographical references and index.
Electronic reproduction.
JSTOR
Keywords: Fall of man in literature; Literature, Modern -- 19th century -- History and criticism; Literature, Modern -- 20th century -- History and criticism; Chute de l'homme dans la littérature.; Littérature -- 19e siècle -- Histoire et critique; Littérature -- 20e siècle -- Histoire et critique; LITERARY CRITICISM / General; Fall of man in literature; Literature, Modern; 1800-1999; Criticism, interpretation, etc